The Relationship of Knowledge Level to Posyandu Cadres Through Infant Massage Practices on Children's Growth in Baluwarti Ward - Warih Anjari Dyah Kusumaning Ayu; Sevy Astriyana (Indonesian Journal of Global Health Research, 2022)
Posyandu health cadres of toddlers who give provide counseling to mothers and children must have sufficient knowledge about growth and development and how to achieve optimal growth and development. Parents, especially mothers, should create a safe and comfortable environment for their children, by doing the right baby massage. Massage is a form of touch therapy that serves as an important treatment technique. Since a newborn is born, parents must full fill the needs of the given to their children, the physical-biological needs for brain growth, the needs of the sensory system, the needs of the motor. Massage given to the babies from birth can provide an inner contact relationship between parents and children giving a feeling of security to babies, massage given to the babies is a very close communication and must be established between mother and baby (Roesli, 2016). The purpose of this study is to determine whether there is a relationship between the knowledge level of Posyandu cadres through the practice of infant massage on the growth and development of children in Baluwarti Village. This type of research is quantitative with this research design using cross sectional. The sample in this study are 30 people. The results showed that the frequency distribution of knowledge is good for 10 (33.3%) people. There is a relationship of knowledge with the implementation of infant massage practice with a p value of 0.000. Based on the results of the study, it is recommended for cadres to be able to practice baby massage, because baby massage have benefits for both the health and the baby's body.